2012
DOI: 10.5194/os-8-931-2012
|View full text |Cite
|
Sign up to set email alerts
|

Surface signature of Mediterranean water eddies in the Northeastern Atlantic: effect of the upper ocean stratification

Abstract: Abstract. Meddies, intra-thermocline eddies of Mediterranean water, can often be detected at the sea surface as positive sea-level anomalies. Here we study the surface signature of several meddies tracked with RAFOS floats and AVISO altimetry.While pushing its way through the water column, a meddy raises isopycnals above. As a consequence of potential vorticity conservation, negative relative vorticity is generated in the upper layer. During the initial period of meddy acceleration after meddy formation or aft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…A key consideration is that a meddy does not travel as an isolated feature but strongly influences the waters above and below (Siedler et al 2005, Bashmachnikov andCarton 2012), to the point that a substantial portion of the water column moves almost jointly with the meddy, behaving very like a Taylor column (Pedlosky 1979, e.g.). However, the water on top of the meddy does not behave as a perfect Taylor column, as otherwise these waters would remain unchanged from the location where the meddy was originally formed, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A key consideration is that a meddy does not travel as an isolated feature but strongly influences the waters above and below (Siedler et al 2005, Bashmachnikov andCarton 2012), to the point that a substantial portion of the water column moves almost jointly with the meddy, behaving very like a Taylor column (Pedlosky 1979, e.g.). However, the water on top of the meddy does not behave as a perfect Taylor column, as otherwise these waters would remain unchanged from the location where the meddy was originally formed, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, as the Meddy sinks deeper, how will the sea surface, containing its signal, change? As discussed in section 1, detecting Meddies using along track satellite altimetry is possible due to the Meddy's vorticity essentially being propagated to the sea surface, creating sea level anomaly sometimes as large as 12 cm [Bashmachnikov and Carton, 2012]. Figure 6b shows the time series of sea surface height anomaly along the path of AMUSE float am110.…”
Section: Horizontal and Vertical Displacement Of A Meddymentioning
confidence: 99%
“…In other words, upperlayer stratification can significantly reduce the intensity of the signal as it reaches the sea surface. The relative vorticity of their surface signals was, on average, from 20.05 to 20.10f (where f is the coriolis parameter, Bashmachnikov and Carton [2012]). Using along-track altimetry, Oliveira et al [2000] showed a 5-10 cm sea level anomaly, and Bashmachnikov and Carton [2012] also reported that the sea level anomaly over Meddies was 6-12 cm with a 70 km Meddy radius for a homogeneous upper layer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations